2016
DOI: 10.1093/femsre/fuw025
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and nitrosative stress defences ofHelicobacterandCampylobacterspecies that counteract mammalian immunity

Abstract: Helicobacter and Campylobacter species are Gram-negative microaerophilic host-associated heterotrophic bacteria that invade the digestive tract of humans and animals. Campylobacter jejuni is the major worldwide cause of foodborne gastroenteritis in humans, while Helicobacter pylori is ubiquitous in over half of the world's population causing gastric and duodenal ulcers. The colonisation of the gastrointestinal system by Helicobacter and Campylobacter relies on numerous cellular defences to sense the host envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 274 publications
(367 reference statements)
0
55
0
Order By: Relevance
“…This protein may also serve the same function in the majority of Helicobacter species, although this has not been well studied since the model species, H. pylori , lacks NrfA and has alternative mechanisms for coping with nitrosative stress (Flint et al, 2016). In contrast to the concatenated protein-based monophyly of the heterotrophs ( Figure 3 ), phylogenetic inference of NrfA reveals at least two independent clades, the first comprising Sulfurospirillum , Wolinella and some Arcobacter , and the second Campylobacter and Helicobacter (Supplementary Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…This protein may also serve the same function in the majority of Helicobacter species, although this has not been well studied since the model species, H. pylori , lacks NrfA and has alternative mechanisms for coping with nitrosative stress (Flint et al, 2016). In contrast to the concatenated protein-based monophyly of the heterotrophs ( Figure 3 ), phylogenetic inference of NrfA reveals at least two independent clades, the first comprising Sulfurospirillum , Wolinella and some Arcobacter , and the second Campylobacter and Helicobacter (Supplementary Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…Genes involved in Campylobacter oxidative stress resistance, as cataloged in a recent review by Flint et al (2016b), were identified in C. coli OR12 and the corresponding protein sequences compared with orthologs from C. jejuni NCTC11168. These data are presented in Supplementary Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…These data are presented in Supplementary Table 1. All the functional genes cataloged by Flint et al (2016b) could be identified with the exception of those encoding the regulators of response to peroxide A and B ( rrpA and rrpB ). No significant sequence similarity to the latter two genes could be identified in the sequences of C. coli OR12 or C. coli RM1875 or C. coli 15-537360.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations